The Influence of Manager's Moral Values on Motivation (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article "Effect of manager's moral value on employee motivation" provides in-depth information about the concept of motivation and its application in the management system. The influence of manager's moral values on employee motivation is an important aspect of organizational dynamics. The article examines the relationship between management ethics and employee motivation in the workplace. In addition, key elements such as leading by example, establishing clear ethical values, creating an inclusive environment, and recognizing and rewarding ethical behavior are emphasized. This highlights the importance of aligning organizational values with personal values to increase employee engagement. It also examines the role of communication, employee induction, and professional development in fostering ethical principles and motivating employees. Overall, this paper provides insight into the complex relationship between management ethics and employee motivation and provides a nuanced understanding of how organizational leaders can positively shape workplace culture through their ethical values.